2019
DOI: 10.1111/nyas.14037
|View full text |Cite
|
Sign up to set email alerts
|

Connecting pancreatic islet lipid metabolism with insulin secretion and the development of type 2 diabetes

Abstract: Obesity is the major contributing factor for the increased prevalence of type 2 diabetes (T2D) in recent years. Sustained positive influx of lipids is considered to be a precipitating factor for beta cell dysfunction and serves as a connection between obesity and T2D. Importantly, fatty acids (FA), a key building block of lipids, are a double‐edged sword for beta cells. FA acutely increase glucose‐stimulated insulin secretion through cell‐surface receptor and intracellular pathways. However, chronic exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 150 publications
(472 reference statements)
1
51
0
Order By: Relevance
“…In the present study, overexpression of Plin5 alleviated palmitateinduced apoptosis, which is consistent with our previous study ( Figure 1A) (26). Interestingly, deletion of Plin5 in INS-1 cells didn't augment lipotoxicity, which may be due to the relatively low expression of Plin5 in pancreatic β-cells compared with other members of Plins family (33). Furthermore, prolonged palmitate treatment resulted in a substantial increase in cytochrome c release from mitochondria and activation of Caspase 3 (Figures 1B,C), aligning with previous reports (34).…”
Section: Plin5 Protects Against Lipotoxicity In Ins-1 β-Cells and Invsupporting
confidence: 92%
“…In the present study, overexpression of Plin5 alleviated palmitateinduced apoptosis, which is consistent with our previous study ( Figure 1A) (26). Interestingly, deletion of Plin5 in INS-1 cells didn't augment lipotoxicity, which may be due to the relatively low expression of Plin5 in pancreatic β-cells compared with other members of Plins family (33). Furthermore, prolonged palmitate treatment resulted in a substantial increase in cytochrome c release from mitochondria and activation of Caspase 3 (Figures 1B,C), aligning with previous reports (34).…”
Section: Plin5 Protects Against Lipotoxicity In Ins-1 β-Cells and Invsupporting
confidence: 92%
“…Of note, PLIN3 is known to have functional redundancy with PLIN2 (18) and is the second most abundant PLIN in mouse islets (4). After down-regulating PLIN2 using siRNA (SiPLIN2) ( Supplementary Fig.…”
Section: Plin2 Deficiency Impaired Insulin Secretion In Ins1 Cells Cumentioning
confidence: 99%
“…The perilipin (PLIN) family of proteins reside on the surface of LDs and regulate intracellular lipid metabolism by controlling the LD formation and mobilization, as well as the interaction with other organelles (11). Among PLINs, PLIN2 is the most abundant PLIN in many non-adipocytes including b cells (4). We previously demonstrated that PLIN2 is increased in parallel to TG accumulation in islets of mice fed HFD, in ob/ob mice, and in human islets after fatty acid (FA) loading (12); findings also reported by others (8,13).…”
Section: Introductionmentioning
confidence: 99%
“…Preferential visceral fat accumulation in early-to-mid gestation T-exposed females likely arises from endogenous hyperandrogenism inhibiting gene expression of a key adipogenic transcription factor, C/EBPalpha [160], thus constraining SC adipocyte maturation and safe lipid storage, while enabling increased lipid accumulation in more pro-lipolytic visceral adipocytes [154,156]. Such AR-mediated distortion of lipid accumulation [26] likely enables hyperlipidemia-associated insulin resistance [154] and pancreatic beta cell compensation, ultimately compromising islet integrity and glucose homeostasis with inevitable progression to T2D [161]. The absence of such lipotoxic progression in late gestation T-exposed female macaques in adulthood may relate to closure of an early-to-mid gestation developmental window for programming of adipose function.…”
Section: Metabolic Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%